The Virtual Space Simulation of the Regional Governance System - Barbakov, Oleg M.; Belonozhko, Marina L.; Siteva, Svetlana S.; Koltunov, Anatoliy L.; Belonozhko, Lidia N. (International Journal of Economics and Financial Issues, 2016)
The article substantiates the study methodology of social experiment in the virtual space within the system of regional governance. It enables to identify the main alternatives in the formulation and decision-making processes of enhancing the effectiveness of administrative structures using automated information technologies and to transfer the results of the virtual experiment to the actual practice of the regional governance system. The authors suggest their own option of the use of a new pattern recognition technology in formulating and solving problems of regional governance, the establishment of information and sociological grounds as the information base for the experiment with managerial interactions in the virtual space. Keywords: regional governance, public administration, pattern recognition JEL Classifications: C6, H72, R58